INTEGRATION OF ISLAMIC EDUCATION VALUES TOWARDS THE “YATIMAN” TRADITION IN THE MONTH OF SURO IN PEKALONGAN - Laela Rohma Puji Lestari; Sopiah Sopiah; Hendri Hermawan Adinugraha (Zawiyah: Jurnal Pemikiran Islam, 2021)
The values of Islamic education are a characteristic, inherent nature which consists of the rules and perspectives adhered to by the Islamic religion. In the “yatiman” tradition of the month of Suro there are Islamic educational values, namely in aqidah, sharia, and morals. Some people in implementing Suroan have mixed with cultural acts, and are against Islam. However, as time goes on, people prioritize something according to Islamic teachings. This study aims to describe the values of Islamic education in the “yatiman” tradition in the month of Suro in Panjang Baru Village, RW IX, Pekalongan City. This study uses a qualitative approach to the type of field research. The data source used is based on the results of observations, interviews conducted with the Long Baru Village Head, the Head of RW IX, Panjang Baru Village, Head of RT, Islamic Religious Leaders, Elders of Panjang Baru Village RW IX, and Orphans, and documentation. Data analysis in this study used a qualitative descriptive through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the “yatiman” “tradition in the month of Suro in Kelurahan Panjang Baru RW IX Pekalongan began with Tahlil, prayer together, and the Suroan night feast then continued with tausiyah activities and donations for orphans the next day. The values of Islamic education are contained in the values of aqidah, sharia values, and moral values.